The Call for the 1976 Democratic National Convention pamphlet - Robert S. Strauss:::::: (1975)
This document is the official Final Call for the 1976 Democratic National Convention, issued by the Democratic National Committee on October 14, 1975. It formally schedules the Convention for July 12, 1976, at Madison Square Garden in New York City to nominate candidates for President and Vice President, adopt the party platform, and conduct other party business. The Call details the allocation of 3,008 delegate votes among the states and territories based on Democratic presidential vote totals and Electoral College strength. It outlines qualifications and selection requirements for state delegations, emphasizing open participation, proportional representation of presidential preferences, and compliance with delegate selection and affirmative action rules. The document also establishes the Convention's standing committees (Platform, Rules, and Credentials), procedural rules for nominations and voting, arrangements and logistical guidelines, and detailed procedures for handling credentials challenges and affirmative action compliance disputes. Overall, it serves as the governing framework for the organization, conduct, and integrity of the 1976 Democratic National Convention.